Ergonomia e design de vestimentas ocupacionais no Brasil: foco em equipamentos de proteção individual no setor de petróleo e gás - Leite, Charles [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The design and deployment of artifacts with incorporated ergonomic properties or atributes, such as protective clothing, from ergodesign principles can serve as a tool to increase productivity, reduce incidents and accidents and improving the quality of life of workers involved in activity. This thesis is based on the principles of Ergonomics and Design, with a view to contributing to the access and dissemination of variables concering a comfortable work clothing for professionals in the oil and gas Brazilian. Wearable interfaces developed without attention to usability requirements lead to poor performance, and a reduction in the quality of the interaction between the subjects and their clothing. Therefore, that, for conducting this research thesis was structured four phases: a literature review, which showed the fragility and low domestic production on the theme. Documentary analysis, which brought together the current legislation and Brazilian standards indentifying certain omission when presented the gaps in effective prevention of incidents and accidents in the workplace. A heuristic evaluation, pointing out weaknesses in the usability of the National System of Management Personal Protective Equipment - PPE and a consultation of stakeholders, when analysis the speech of the institutions and agents responsible for regulating the protective clothing, target of this investigation, and pointed out certain inconsistencies

A concepção e disponibilização de artefatos com propriedades ou atributos ergonômicos incorporados, como vestimentas de proteção, a partir dos princípios do ergodesign podem servir como instrumento para aumento de produtividade, redução dos incidentes e acidentes de trabalho e melhoria da qualidade de vida dos trabalhadores envolvido na atividade. Esta investigação de tese é pautada nos princípios do Ergonomia e Design, com vistas a colaborar para o acesso e disseminação das variáveis concernentes a um confortável vestuário laboral para profissionais do setor de petróleo e gás brasileiro. Interfaces vestíveis desenvolvidas sem o atendimento aos requisitos de usabilidade levam a um desempenho deficiente, além de uma redução da qualidade da interação sujeito e vestimenta. De forma que, para condução da investigação da tese, estruturou-se a pesquisa dividida em quatro fases: um levantamento bibliográfico, que apontou a fragilidade e pouca produção tipicamente nacional sobre o assunto; uma análise documental, que reuniu a legislação e normas brasileiras vigentes identificando certa omissão ao apresentar lacunas na efetiva prevenção de incidentes e acidentes no âmbito laboral; uma avaliação heurística, apontando fragilidades na usabilidade do sistema nacional de gerenciamento de Equipamentos de Proteção Individual - EPI; e uma consulta a stakeholders, que analisou o discurso das instituições e os agentes responsáveis pela regulação dos vestuários de proteção, alvo desta investigação e apontou certas incongruências
Ergonomics and design of protective clothing in Brazil: focus on personal protective equipment in the oil and gas sector
Keywords: Vestuario; Uniformes; Ergonomia; Desenho industrial; Moda; Clothing and dress